Analysis of Macroeconomic Influence, Investment Decisions, and Funding Decisions on Profitability, Unsystematic Risk, and Sharia Stock Return (Study of 70 JII Shares Listed on the IDX) - Pradhani, Tri Buana Wira; Ratnawati, Tri; Brahmayanti, I.A. Sri (PT Inovasi Pratama Internasional, 2024)
This research aims to examine and analyze the influence of macroeconomics, investment decisions and funding decisions on profitability, unsystematic risk and returns on JII 70 shares listed on the Indonesia Stock Exchange from 2019 to 2023. This research uses a quantitative approach and this type of research This is explanatory causal research which will explain the cause-and-effect relationships between research variables. The population used in this research is JII 70 shares listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling technique in this research uses a purposive sampling technique, with the sample used being 20 companies with listed JII 70 indexed shares. on the Indonesian Stock Exchange from 2019 to 2023. The data source in this research is secondary data obtained from the official publication website of Bank Indonesia, the Central Statistics Agency, and the Indonesian Stock Exchange. Hypothesis testing was carried out by testing the SEM-PLS structural model using the Smart-PLS4 application. Based on the results of data testing, a conclusion regarding hypothesis testing is obtained, namely, macroeconomics does not have a significant effect on profitability, unsystematic risk and stock returns. Investment decisions have a positive and significant effect on profitability, unsystematic risk and stock returns. Funding decisions have a positive and significant effect on profitability, but have a negative and significant effect on unsystematic risk and stock returns. Profitability has a positive and significant effect on stock returns, and unsystematic risk has a negative and significant effect on stock returns.